The Unstable Macroeconomic Factors and Bank Profitability in FCC Area: A Conceptual Framework - Salem, Salem Mohammad Abdelaziz (Akademia Baru, 2018)
The aim of this paper is to discuss at a conceptual level the relationships between the important macroeconomic factors and banks' profitability in the troublous Fertile Crescent Countries (FCC). The instability in the macroeconomic environment is dominating FCC area, especially in the last two decades affecting banking industry. The variables proposed under examination are interest rate, exchange rate, economic growth, inflation rate, and money growth. The model of this study if validated would have significance important policy implications to the governments of FCC and other stakeholders. Thus, the proposed conceptual framework which is drawn upon the existing literature has examined the effect of unstable macroeconomic factors on banks' profitability in FCC countries such as Palestine, Jordan, and Lebanon. The previous studies showed mix and inconclusive results on the effect of macroeconomic factors and banks' profitability. This paper contributes to the existing literature by providing a conceptual arguments that allow for better understanding of the impact of the unstable macroeconomic environment on the profitability of banking industry.